Advancing stroke recovery: unlocking the potential of cellular dynamics in stroke recovery - Keivan Sahebi; Hassan Foroozand; Mobina Amirsoleymani; Saghi Eslamzadeh; Manica Negahdaripour; Amir Tajbakhsh; Abbas Rahimi Jaberi; Amir Savardashtaki (Cell Death Discovery, 2024)
Abstract Stroke stands as a predominant cause of mortality and morbidity worldwide, and there is a pressing need for effective therapies to improve outcomes and enhance the quality of life for stroke survivors. In this line, effective efferocytosis, the clearance of apoptotic cells, plays a crucial role in neuroprotection and immunoregulation. This process involves specialized phagocytes known as “professional phagocytes” and consists of four steps: “Find-Me,” “Eat-Me,” engulfment/digestion, and anti-inflammatory responses. Impaired efferocytosis can lead to secondary necrosis and inflammation, resulting in adverse outcomes following brain pathologies. Enhancing efferocytosis presents a potential avenue for improving post-stroke recovery. Several therapeutic targets have been identified, including osteopontin, cysteinyl leukotriene 2 receptor, the µ opioid receptor antagonist β-funaltrexamine, and PPARγ and RXR agonists. Ferroptosis, defined as iron-dependent cell death, is now emerging as a novel target to attenuate post-stroke tissue damage and neuronal loss. Additionally, several biomarkers, most importantly CD163, may serve as potential biomarkers and therapeutic targets for acute ischemic stroke, aiding in stroke diagnosis and prognosis. Non-pharmacological approaches involve physical rehabilitation, hypoxia, and hypothermia. Mitochondrial dysfunction is now recognized as a major contributor to the poor outcomes of brain stroke, and medications targeting mitochondria may exhibit beneficial effects. These strategies aim to polarize efferocytes toward an anti-inflammatory phenotype, limit the ingestion of distressed but viable neurons, and stimulate efferocytosis in the late phase of stroke to enhance post-stroke recovery. These findings highlight promising directions for future research and development of effective stroke recovery therapies.